2020
DOI: 10.1136/emermed-2019-208797
|View full text |Cite
|
Sign up to set email alerts
|

Measuring ‘Need for Recovery’ as an indicator of staff well-being in the emergency department: a survey study

Abstract: BackgroundThe Need for Recovery (NFR) Scale is an 11-item questionnaire that assesses how work affects intershift recovery. Items are summated to form a score with a maximum value of 100. Previously reported scores range from 38 in nurses to 55 in miners. This study aimed to determine the NFR Score among ED staff and to identify whether the NFR Score was associated with characteristics potentially implicated with recovery from work. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The reported rates of distress and trauma do not take account of any pre-existing psychiatric morbidity or historical factors that may predispose doctors to developing mental health difficulties in these circumstances. [63][64][65][66] Data were gathered with regard to historical trauma, one of the most significant predictors of mental health difficulties long-term. Furthermore, while the sample size is large, any self-reporting measure is open to selection bias.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…The reported rates of distress and trauma do not take account of any pre-existing psychiatric morbidity or historical factors that may predispose doctors to developing mental health difficulties in these circumstances. [63][64][65][66] Data were gathered with regard to historical trauma, one of the most significant predictors of mental health difficulties long-term. Furthermore, while the sample size is large, any self-reporting measure is open to selection bias.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“… 35 36 Our findings are, however, congruent with our own feasibility work completed in a single-centre UK ED, reporting a median NFR Score of 81.8 in all staff groups. 21 The impact of rising patient numbers and overcrowding on UK and Ireland EDs is commonly reported, 38 39 but our findings are the first to illustrate the impact of high work demand on physicians’ need to recuperate from work and the modifiable factors which can mitigate this fatigue.…”
Section: Discussionmentioning
confidence: 63%
“… 28 Following a minor amendment to one question to increase applicability to the study population (from ‘after the evening meal, I generally feel in good shape’ to ‘after my breaks, I feel fresh to continue my work’), feasibility work in a single UK centre demonstrated a Cronbach’s alpha of 0.79, and found that the NFR Scale was acceptable and user friendly. 21 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations